Trauma Vaskular: Patofisiologi, Manifestasi Klinis, Diagnosis dan Penatalaksanaan - Zhayyin Palna; I Gede Aditya Satrya Bhuwana Cakra; Irsyadina Hasana Bharata; Khaula Karima; Salsabila Chauna; Wina Arsylia Fakar; Maz Isa Anshori Arsatt (Lombok Medical Journal, 2024)
Vascular trauma is an injury involving the circulatory system, particularly blood vessels, disrupting the body's balance and being a leading cause of morbidity and mortality. The extremities are the most common locations for vascular trauma, especially the femoral artery, popliteal artery, and brachial artery. Signs and symptoms of vascular trauma in body limbs are described as hard and soft signs. Hard signs found in patients indicate the need for surgical intervention, while patients with soft signs require further diagnostic imaging for confirmation. Management should consider the golden period (6 to 8 hours) by controlling bleeding with resuscitative endovascular balloon occlusions (REBOA), minimizing ischemic events in the distal part of the trauma, and preventing compartment syndrome. Surgical intervention is performed to achieve functional recovery and salvage the affected vascular area. Surgical procedures that can be performed in cases of vascular trauma include vascular grafting, vascular ligation, and temporary intravascular shunt (TIVS).